The propulsion performance of the semi-active tandem flapping foils for wave gliders: A study on vortex interactions and hydrodynamic performance - Qi, Zhanfeng; Xing, Ziwen; Qiao, Yanan; Zhang, Xueqi; Qin, Yufeng; Feng, Zhitao (Ocean engineering, 2024)
An investigation is conducted on the propulsion performance of semi-active flapping foils in tandem configuration of the wave glider, considering different vortex effects and tandem distances. The Finite Volume Method is utilized with commercial CFD software Fluent to solve the URANS equations around the flapping foil. A mesh comprising a 2D NACA0012 foil with Reynolds number Re = 42,000 is used in all simulations. The study investigates the propulsion performance of tandem flapping foil systems, focusing on the differing impacts of wave interaction on the front and rear foils. It explores how varying tandem distances and reduced frequencies influence thrust enhancement and degradation. The research reveals that while the front foil consistently benefits from thrust enhancement, the rear foil's performance is more complex, being subject to thrust enhancement or reduction due to wake vortex interactions. Detailed analyses of instantaneous thrust coefficients, pitching trajectories, and pressure contours provide insights into the hydrodynamic performance of these systems. The findings emphasize the importance of synchronization in motion between the foils for optimal propulsion and highlight the rear foil's susceptibility to changes in the wake flow, affecting its thrust generation capability. Thus, the optimal tandem distance can fully capitalize on the thrust enhancement effect of the wake interaction to improve the performance of the tandem flapping foil propulsion system. •Semi-Active Tandem Flapping Foils: The research centers on the propulsion performance of semi-active tandem flapping foils in tandem configurations for wave gliders.•Front and Rear Foil Dynamics: Explores how thrust enhancement and degradation are influenced by tandem distances and reduced frequencies, noting distinct effects on front and rear foils.•Wake Vortex Interactions: Highlights the complex performance of the rear foil due to wake vortex interactions and the importance of motion synchronization.•OptimalTandem Distance: Concludes that optimal tandem distance significantly improves propulsion performance by maximizing the thrust enhancement effect of wake interactions.